Twenty-four-hour systolic blood pressure variability and renal function decline in elderly male hypertensive patients with well-controlled blood pressure - Wang X (Dove Medical Press, 2018)
Xi Wang, Fan Wang, Minzhi Chen, Xiaona Wang, Jin Zheng, Aimei Qin Department of Geriatric Cardiology, Chinese PLA General Hospital, Beijing, China Purpose: Increased variability in blood pressure (BP) is known to be closely associated with the development, progression and severity of renal damage in patients with chronic kidney disease. However, little is known about the association of BP variability (BPV) with the decline of renal function in elderly hypertensive patients with well-controlled BP. We, therefore, aimed to investigate the association between BPV and glomerular filtration rate in hypertensive elderly (age >60 years) and very elderly (age >80 years) male patients with BP controlled within the normal range by antihypertensive therapy.Patients and methods: This study involved 484 hospitalized elderly male hypertensive patients with BP controlled within the normal range by antihypertensive therapy. BPV was defined as the SD from mean BP over a 24 h period. Renal function was estimated by estimated glomerular filtration rate (eGFR) which was calculated by the Chinese modified Modification of Diet in Renal Disease Equation. Participants were divided into three groups according to their eGFR data. Multivariate linear regression was then used to analyze the correlation between eGFR and BPV.Results: The 24 h systolic BP (SBP) variability increased as eGFR decreased. There was no significant difference in 24 h SBP variability when compared between elderly and very elderly hypertensive patients. Multivariate linear regression analysis showed that SBP variability demonstrated a negative linear relationship with eGFR (P<0.05) after adjustment for potential confounding factors.Conclusion: Among the parameters of 24 h ambulatory BP monitoring, 24 h SBP variability is the only independent risk factor for a decline in renal function in elderly and very elderly male hypertensive patients with well-controlled BP. Keywords: hypertension, elderly male, blood pressure variability, estimated glomerular filtration rate